Des usages et des stratégies d’appropriation - Amor Ben Amor (Communication)
In this article the author raises the question of the appropriation of the cell phone by Tunisian junior managers recently settled in the capital city of Tunis from rural and semi-rural areas. Analysis reveals the use of cell phones as a tool to better adapt to their new social environment of family, marriage, religion, workplace and social networks. The use of cell phones falls under a strategy of continuous negotiation between contrary and sometimes contradictory behaviour and values in order to establish, for a period of time and in a cumulative way, levels of an acceptable compromise.